1986
DOI: 10.1017/s0043174500067151
|View full text |Cite
|
Sign up to set email alerts
|

Control of Triazine-Resistant Common Lambsquarters (Chenopodium album) and Two Pigweed Species (Amaranthusspp.) in Corn (Zea mays)

Abstract: Various chemical treatments were evaluated over two growing seasons for control of triazine-resistant common lambsquarters (Chenopodium albumL. # CHEAL) and for control of a triazine-resistant infestation containing both redroot pigweed (Amaranthus retroflexusL. # AMARE) and Powell amaranth (A. powelliiS. Wats. # AMAPO). Atrazine [6-chloro-N-ethyl-N′-(1-methylethyl)-1,3,5-triazine-2,4-diamine], cyanazine {2-[[4-chloro-6-(ethylamino)-1,3,5-triazin-2-yl] amino]-2-methylpropanenitrile}, and metribuzin [4-amino-6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Pendimethalin provided greater (98%) and more consistent control of TR-CHEAL than metolachlor or acetochlor. Other researchers have reported similar results with pendimethalin applied PRE (Fuerst et al 1986;Myers and Harvey 1993).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Pendimethalin provided greater (98%) and more consistent control of TR-CHEAL than metolachlor or acetochlor. Other researchers have reported similar results with pendimethalin applied PRE (Fuerst et al 1986;Myers and Harvey 1993).…”
Section: Resultssupporting
confidence: 76%
“…Triazine-resistant common lambsquarters (TR-CHEAL) is widespread throughout Michigan and the north-central United States. Numerous studies have reported satisfactory control of TR-CHEAL with various preemergence (PRE) herbicides (Darmency and Gasquez 1990;Fuerst et al 1986;Hagood 1989;Myers and Harvey 1993;Parks et al 1996). However, an increased understanding of PRE herbicides that consistently control TR-CHEAL in corn is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Control of TR-CHEAL with preemergence (PRE) ap-plications of pendimethalin has varied. Fuerst et al (1986) and Myers and Harvey (1993) obtained satisfactory control of TR-CHEAL with PRE applications of pendimethalin, whereas Hagood (1989) did not. In the Virginia study, a PRE application of pendimethalin followed by a POST application of pendimethalin was required to obtain 87% control or better by the final evaluation (Hagood 1989).…”
Section: Introductionmentioning
confidence: 93%
“…Myers and Harvey (1993) found that POST applications of dicamba, thifensulfuron, pendimethalin, pyridate, and 2,4-D amine were most effective in the control of TR-CHEAL. Fuerst et al (1986) and Parks et al (1995) found that POST applications of dicamba or bromoxynil provided good control of TR-CHEAL. Glenn et al (1997) reported that POST applications of nicosulfuron or primisulfuron tank-mixed with 2,4-D or dicamba provided excellent late-season control of TR-CHEAL.…”
Section: Introductionmentioning
confidence: 99%
“…PRE applications of atrazine have also failed to control several other weed species, such as common groundsel ( Senecio vulgaris L.), common lambsquarters ( Chenopodium album L.), hood canarygrass ( Phalaris paradoxa L.), rigid ryegrass ( Lolium rigidum Gaudin), and blackgrass ( Alopecurus myosuroides Huds.) that have evolved resistance to atrazine applied POST (Fuerst et al 1986; Ryan 1970; Yaacoby et al 1986). The GR 50 values for atrazine applied PRE for the S and MR Palmer amaranth populations were 0.035 and 3.93 kg ha −1 , respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%